Knowledge And Self-Efficacy On “First Responder” In Giving First Aid - Nadiya Miftah Karima; Aan Nuraeni; Ristina Mirwanti (Journal of Nursing Care, 2019)
Introduction: “First responder” is a lay person who get trained to do first aid. Doing first aid is influenced by knowledgeand self-efficacy of the helper. However, the study of knowledge and self-efficacy of first aid providers is limited. Thisstudy aimed to asses the knowledge and self-efficacy of first responders in doing first aid. Method: This research usedquantitative description method with cross sectional approach towards 65 first responder in a University in Bandung.The samples were selected using total sampling technique. The data were gathered using questionnaire of FirstAid Knowledge and Wilderness First Self-efficacy Scale. The data were analyzed through quantitative descriptionanalysis, including mean and frequency distribution. Result : The research found that 57 respondents (87,7%) hadlimited knowledge of first aid, in particular about health problems related to environment aspects. Meanwhile 62respondents (95,5%) %) had high self-efficacy especially on the ability to assess vital signs, yet they had low selfefficacy on conduct a spinal assessment (4.5%). Conclusion: There is needs for increasing knowledge about healthproblem related to the environment and self-efficacy about spinal assessment by providing materials and other kindsof learning methods aside from lectures, educational practice as well as experimental learning and simulations.In addition, first responders also need to improve their ability related environment aspects and spinal assessment.